(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This article introduces a new approach for digital misinformation detection with the application of Neutrosophic Hesitance Distance Measures. Including hesitance values in neutrosophic similarity and distance measurement helps us to deal with uncertainty and vagueness better. Complement, max, min, and max-min operations are explained along with definitions. An example provides a glimpse of how Neutrosophic Set Hesitance Distance Measure enhances decision-making for detecting misinformation on social media. The findings identify the benefits of merging hesitance into neutrosophic fuzzy systems to achieve more precise and reliable analysis.